Supramolecular Polymers Based on Efficient Pillar[5]arene—Neutral Guest Motifs. Issue 36 (6th August 2013) - Li, Chunju; Han, Kang; Li, Jian; Zhang, Yanyan; Chen, Wei; Yu, Yihua; Jia, Xueshun
<x xml:space="preserve">Abstract</x> Neutral and efficient: A neutral guest with a cyano site and a triazole site, which can be easily prepared and modified, is demonstrated to strongly bind with pillar[5]arene (see figure). Based on this new recognition motif, two neutral supramolecular polymers in organic media, which are currently unfeasible by means of host–guest interactions of crown ethers and calixarenes, were fabricated. One is AA/BB‐type, and the other is A2/B3‐type.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>